'At the Mercy of the German Eagle': Images of London in Dissolution in the Novels of William Le Queux. Issue 1 (1st June 2020) - Taylor, Antony
Abstract: In the years before 1914 the novels of William Le Queux provided a catalyst for British debates about the economic, military and political failures of the empire and featured plots that embodied fears about new national and imperial rivals. For Le Queux, the capture of London was integral to German military occupation. Representative of the nation's will to resist, or its inability to withstand attack, the vitality of London was always at issue in his novels. Drawing on contemporary fears about the capital and its decay, this article considers the moral panics about London and Londoners and their relationship to Britain's martial decline reflected in his stories. Engaging with images of anarchist and foreign terrorism, and drawing on fears of covert espionage rings operating in government circles, this article probes the ways in which Le Queux's fiction expressed concerns about London as a degenerate metropolis in the process of social and moral collapse.